Pendampingan Pencatatan Akuntansi Sederhana pada Pemilik UKM Kerupuk Singkong di Desa Sawojajar - Darwin Warisi (Jurnal Kabar Masyarakat, 2024)
The cassava chips industry is a home or family industry which makes this industry a source of family income as well as a milestone in the community's economic cycle. The importance of this industry is unfortunately not accompanied by the ability of business actors to carry out optimal financial records, whereas accounting recording activities are an important activity in the management process of a company. business. With the assistance activities carried out by the community service team regarding financial recording, business actors can increase their understanding of simple financial recording. The results of the activities carried out are The owner of the cassava chips business "Dwi Putri" stated that he was able to carry out financial records in the business process, and was good at calculating sales profits.